A Comparison of the Returns of Oil and Energy Companies Quoted in Kase and the Returns of the Kase Index, Exchange Rate, and Selected International Energy Indices - Izatullayeva, Bibigul; Tayauova, Gulzhanat; Sadykova, Gulnara; Toktibayeva, Madina; Kenzhaliyev, Altynbek (International Journal of Energy Economics and Policy, 2023)
The positive steps taken since the beginning of the 2000s have brought Kazakhstan’s economy ahead of its peers. Making this economic growth sustainable depends on the correct determination of the interaction between economic instruments. Therefore, we aim to determine the relationship between the returns of oil and energy companies traded on the Kazakhstan Stock Exchange (KASE) and the returns of the KASE index, exchange rate, and selected international energy indices. The data were analyzed using the VAR method. Our analysis showed that the two-period lagged value of the KZTO variable, the one-period lagged return of the KASE index in the KZAP variable, the two-period lagged return of the dollar exchange rate and the two-period lagged return of the KZAP in the KEGC variable have positive effects. On the other hand, one-period lagged return of the FTSE CNBC Asia 100 Oil & Gas index, one-period, and two-period lagged return of the ruble return, and one-period lagged return of the Dow Jones Islamic Markets Oil & Gas index were found to have negative effects.